GTP hydrolysis by Ran occurs at the nuclear pore complex in an early step of protein import - Melchior, Frauke; Guan, Tinglu; Yokoyama, Nobuhiko; Nishimoto, Takeharu; Gerace, Larry (The journal of cell biology, 1995)
Mediated import of proteins into the nucleus involves multiple cytosolic factors, including the small GTPase Ran. Whether Ran functions by interacting with other cytosolic proteins or components of the nuclear pore complex has been unclear. Furthermore, the precise transport step where Ran acts has not been determined. To address these questions, we have analyzed the binding interactions of Ran using permeabilized cells and isolated nuclear envelopes. By light and electron microscope immunolocalization, we have found that Ran accumulates specifically at the cytoplasmic surface of the nuclear pore complex when nuclear import in permeabilized cells is inhibited by nonhydrolyzable analogs of GTP. Ran associates with a peripheral pore complex region that is similar to the area where transport ligands accumulate by depletion of ATP, which arrests an early step of transport. Binding studies with isolated nuclear envelopes in the absence of added cytosol indicate that Ran-GTP directly interacts with a pore complex protein. Using blot overlay techniques, we detected a single prominent polypeptide of isolated nuclear envelopes that binds Ran-GTP. This corresponds to the 358-kD protein RanBP2, a Ran binding pore complex protein recently identified by two-hybrid screening. Thus, RanBP2 is likely to constitute the Ran-GTP-binding site detected at the cytoplasmic periphery of the pore complex. These data support a model in which initial ligand binding to the nuclear pore complex occurs at or near RanBP2, and that hydrolysis of GTP by Ran at this site serves to define commitment to the nuclear import pathway.